Comparison of prepartum blood parameters in dairy cows with postpartum ketosis and new risk prediction candidates - Choi, Woojae; Ro, Younghye; Choe, Eunhui; Hong, Leegon; Kim, Dohee; Kim, Seongdae; Yoon, Ilsu; Kim, Danil (Frontiers in Veterinary Science, 2023)
Ketosis is a predominant metabolic problem and a risk factor for several postpartum diseases. This retrospective study aimed to evaluate the complete blood count (CBC), plasma biochemistry, and osteocalcin and identify significant prepartum and early postpartum values expressed in ketotic cows. In 135 Holstein Friesian cows, 210 parturitions of 114 primiparous and 96 multiparous cows were examined. According to the plasma concentrations of β-hydroxybutyrate (BHB; ≥ 1.4 mmol/L) or non-esterified fatty acids (NEFA; ≥ 0.7 mmol/L) in the postpartum period, cows were divided into healthy cows (CON) and ketotic cows (KET). Analyses of CBC and biochemistry profiles were performed from –6 to 4 weeks of parturition every two weeks (prepartum; BW–5, BW–3, and BW–1, postpartum; BW1 and BW3), and osteocalcin ELISA tests were performed using blood samples from –2 to 2 weeks of parturition (BW–1 and BW1). In primiparous KET (n = 114) before parturition, lower lymphocyte (Lym) in BW–5 and BW–3, lower red blood cell (RBC) in BW–5, higher mean corpuscular volume (MCV) in BW–1, and higher NEFA in BW–3 were significant compared with CON. Primiparous KET showed lower carboxylated osteocalcin (cOC) levels and a significant decrease after parturition. In multiparous KET (n = 96) before parturition, lower neutrophil (Neu) in BW–5, higher hemoglobin (HGB) in BW–5, higher MCV in BW–5 and BW–1, higher mean corpuscular hemoglobin (MCH) in BW–5, lower total cholesterol (TC) in BW–5, higher triglyceride (TG) in BW–3, higher NEFA in BW–1, higher glucose (Glu) in BW–3, lower γ-glutamyl transferase (GGT) in BW–5, lower inorganic phosphate (iP) in BW–3, and higher body condition score (BCS) in BW–5 and BW–3 were significant compared with CON. Multiparous KET showed decreased cOC and uncarboxylated osteocalcin (ucOC) after parturition, which was lower than that in the CON group. The blood parameters expressing different values between CON and KET in prepartum or early postpartum periods are presumed to show individual nutrition and health states, liver function, and overweight status. These parameters could be valuable indicators that can be used to prevent the occurrence of ketosis and improve management practices by recognizing these differences in ketotic cows before calving.